Integrated Use of Multitrophic Aquaculture Resources in the Recreational Business - SHISHANOVA, Elena Ivanovna; BAGDASARIAN, Aleksandr Sergeevich; SEMAK, Anna Eduardovna; FROLOV, Alexander Lvovich; SHARONIN, Pavel Nikolaevich (Journal of Environmental Management and Tourism; Vol 11 No 3 (2020): JEMT Volume XI Issue 3(43) Summer 2020DO - 10.14505//jemt.v11.3(43).25, 2020)
The article deals with the development of approaches to the integrated use of multitrophic aquaculture resources in the recreational business. It is revealed that multitrophic aquaculture allows successfully combining several areas in nature management. This includes obtaining high-quality food products (both of animal and plant origin), protecting and growing valuable medicinal plants, expanding the area of melliferous plants, and cultivating various industrial crops. It is proved that fish farming, often being extensive, can be considered as a kind of organic farming in the framework of recreational projects using multipurpose reservoirs. It is revealed that reservoirs used in recreational business, as well as the territories directly adjacent to them, are often characterized by an increased level of biodiversity that allows considering such territorial complexes as important stabilizing ecological zones.